Exergoeconomics of sugar juice heat exchangers - Gabriel García, Ulises; Cruz Fonticiella, Oscar M.; Moya Rodríguez, Jorge L.; Betancourt Mena, Jesús (Centro Azúcar Journal, 2007)
Using the exergoeconomic concept, through the Exergetic Cost Theory, the exergetic unit costs and exergoeconomic unit costs are determined for mixed sugar juice heat exchangers, extensively used in the Sugar Industry. In a later work the minimization of these costs is approached.